Pendampingan Kegiatan Lembaga Sertifikasi Kompetensi (LSP) SMK Al-Muhtadin - Endang Supriyadi; Maya Sofiana; Rita Wahyuni (Jurnal Komunitas : Jurnal Pengabdian kepada Masyarakat, 2021)
The problem faced by the newly established professional certification institutions, especially LSP Al-Muhtadin, located in Cipayung, Depok, West Java, is the lack of knowledge of institutional management, therefore this assistance activity aims to improve the skills of production teachers as assessors in carrying out competency test assessments for students majoring automation of office governance (OTKP) and computer network engineering (TKJ) in accordance with BNSP standards and administrative management. The methods used are lectures, practice, and question and answer. From the results of these activities, these activities resulted in enhancment knowledge and understanding of teachers and administrators link to each other to material in the form of theory and practice as well as increased abilities in administrative management and competency test assessment processes